Elected Women Panchayat Samiti: An Structural Arrangement for Farm Women Empowerment in India - Anuradha Ranjan Kumari , S. K. Dubey; US Gautam (Indian Journal of Extension Education, 2016)
Women represent almost half of the human resources and half the potential in all the societies. India being no exception to it and, therefore, the employment and autonomy of women and level of women’s social achievement are the indicators of sustainable development. Empowerment is a process, not an event, which challenges traditional power equations and relations. Abolition of gender-based discrimination in all institutions and structures of the society and participation of women in policy and decision making process at domestic and public levels are few dimensions of women empowerment. The present study was an effort to know the extent of empowerment and associated problem of elected women members in Panchayati Raj institutions. Total Twenty Three women representatives were randomly sampled from Pusa and Kalyanpur block of Samastipur district in Bihar province in Indiafrom the 40 randomly drawn villages from the two selected blocks of the above districts. The tool used for collecting information was pre-structured interview schedule and data were collected through personal interview method. In order to determine the conditions sowing the empowerment of women the data were subjected to correlation and multiple regressions analysis. Their extent of empowerment was taken as dependent variables. The finding revealed that 21.73 percent of the respondents were highly empowered with respect to “Health welfare and Development of Public Property.The association between empowerment and farm womens’ age was negative but highly significantly associated (P<0.01). The results of correlation and multiple regression analysis between empowerment and Socio-economic & Psychological Variables of elected women PanchayatSamiti members was highly significant with variables like caste, family size, family income and interaction style (P,0.01). The partialregression coefficient were significant only in case of two variable i.e. caste and age.